Reconstruction of Structured, Systematic and Massive Election Administration Violations In The Framework of The Judicial System - Kurnia, Kamal Fahmi; Rusjana, Muhamad; Hendryan, Dery (Universitas Malayati, 2024)
In the implementation of the General Election in Indonesia, there are several legal instruments that regulate the types of violations of the Election law. This type of violation becomes an interesting discussion to discuss because if the candidate participating in the election is proven, the sanction is disqualification. Bawaslu has the authority to handle election administration violations by structured, systematic, massive. In the handling process, the Bawaslu Commissioner acts as a panel of judges. The process of recruiting Bawaslu Commissioners is not oriented as a panel of judges in conducting trials, but as a supervisory institution in the administration of elections. So that there is a shift in the function of Bawaslu not only as a supervisory institution but into a judicial institution. Constitutionally, Bawaslu is not an institution of Judicial Power. So, in the Judicial System paradigm, this has the potential to reduce the quality in deciding alleged violations of the structured, systematic, massive election administration. The problem in this research is how is the concept of election administration violation by structured, systematic, massive in Indonesia? And how is the concept of handling election administration violations in a structured, systematic, massive manner in accordance with the framework of the judicial system in Indonesia?This research method uses a normative juridical approach, with secondary data as the main data type. The data collection method was carried out by means of a library study of relevant primary, secondary and tertiary legal materials. Furthermore, data analysis was carried out using descriptive analysis method.The conclusion of this study states that the concept of election administration violations by structured, systematic, massive in Indonesia is one type of special election administration violation with the handling authority owned by Bawaslu. The concept of handling election administrative violations by structured, systematic, massive which is in line with the framework of the judicial system in Indonesia, namely through a special election judiciary that administers justice with an ad hoc panel of judges for handling structured, systematic, massive violations of election administration in Indonesia.Keywords: Reconstruction, Election Administration, Judicial System